1985
DOI: 10.1001/archinte.145.8.1429
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole-induced increase in estradiol-testosterone ratio. Probable explanation for gynecomastia

Abstract: Ketoconazole, an antifungal drug, causes gynecomastia in some patients. It also inhibits androgen and glucocorticoid synthesis. In four volunteer male subjects, 600-mg doses of ketoconazole depressed serum testosterone concentrations markedly, but serum estradiol to a much lesser degree. The bound and free percentages of both hormones were not significantly altered. The net result was a significant elevation of the estradiol-testosterone ratio, expressed as either total circulating hormone or free hormone. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A larger decrease of E2 levels might have been expected knowing that plasma T is a major precursor for E2 synthesis. However, also in previous studies using KTZ, a mild or absent effect on E2 levels has been reported 29,30 . The E2 levels may have weakened the modulating effect of T on LH release in our subjects.…”
Section: Discussionsupporting
confidence: 52%
“…A larger decrease of E2 levels might have been expected knowing that plasma T is a major precursor for E2 synthesis. However, also in previous studies using KTZ, a mild or absent effect on E2 levels has been reported 29,30 . The E2 levels may have weakened the modulating effect of T on LH release in our subjects.…”
Section: Discussionsupporting
confidence: 52%
“…In patients receiving higher dosages (800 to 1200 mg/day), the incidence approaches 21 % (Pont et al 1984). Pont et al (1985) have shown that ketoconazole, by virtue of its selective effect on testosterone synthesis, causes a significant rise in estradioltestosterone ratio in both male volunteers and men receiving long term therapy. This selective hormonal effect may explain the development of gynaecomastia.…”
Section: Hormonal Effectsmentioning
confidence: 99%
“…Ketoconazole is less specific in its action than some of the newer azoles. This accounts for some of its endocrine effects, including altered adrenal hormone and cholesterol metabolism, gynaecomastia (Pont et al 1985) and impotence. Nausea, vomiting, pruritus, abdominal pain, diarrhoea, headache, urticaria and dizziness have all been reported, but are all uncommon, with the exception of nausea (3 to 10%) [Van Tyle 1984].…”
Section: Candidiasismentioning
confidence: 99%